Eso Astrophysics Symposia
DOI: 10.1007/10828549_16
|View full text |Cite
|
Sign up to set email alerts
|

Type Ia Supernovae: Progenitors and Diversities

Abstract: A key question for supernova cosmology is whether the peak luminosities of Type Ia supernovae (SNe Ia) are sufficiently free from the effects of cosmic and galactic evolution. To answer this question, we review the currently popular scenario of SN Ia progenitors, i.e., the single degenerate scenario for the Chandrasekhar mass white dwarf (WD) models. We identify the progenitor's evolution with two channels: (1) the WD+RG (red-giant) and (2) the WD+MS (near main-sequence He-rich star) channels. The strong wind … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 42 publications
2
56
0
Order By: Relevance
“…In this model, a CO WD increases its mass by accreting hydrogen-or helium-rich matter from its companion, and explodes when its mass approaches the Chandrasekhar mass limit. The companion may be a main-sequence star (WD+MS) or a red-giant star (WD+RG) (Yungelson et al 1995;Li et al 1997;Hachisu et al 1999a,b;Nomoto et al 1999Nomoto et al , 2003Langer et al 2000;Han & Podsiadlowski 2004;Chen & Li 2007Han 2008;Meng et al 2009;Meng & Yang 2010a;Lü 2009;Wang et al 2009bWang et al , 2009cWang et al , 2010. The SD model has also been verified by many observations (see Meng & Yang 2010b).…”
Section: Introductionmentioning
confidence: 80%
“…In this model, a CO WD increases its mass by accreting hydrogen-or helium-rich matter from its companion, and explodes when its mass approaches the Chandrasekhar mass limit. The companion may be a main-sequence star (WD+MS) or a red-giant star (WD+RG) (Yungelson et al 1995;Li et al 1997;Hachisu et al 1999a,b;Nomoto et al 1999Nomoto et al , 2003Langer et al 2000;Han & Podsiadlowski 2004;Chen & Li 2007Han 2008;Meng et al 2009;Meng & Yang 2010a;Lü 2009;Wang et al 2009bWang et al , 2009cWang et al , 2010. The SD model has also been verified by many observations (see Meng & Yang 2010b).…”
Section: Introductionmentioning
confidence: 80%
“…A different ejection channel is provided by the SN Ia that are believed to arise from thermonuclear explosions of white dwarfs (WD hereafter) in binary stellar systems as a consequence of the matter accretion from the companion (e.g., Nomoto et al 2000). However, there are still a number of uncertainties about the nature of both the WD and the companion and about the mass reached at the onset of the explosion (e.g., Matteucci and Recchi 2001;Yungelson and Livio 2000).…”
Section: What Is a Model Of Chemical Evolution?mentioning
confidence: 99%
“…Following Greggio and Renzini (1983), we assume here that SN Ia arise from stars belonging to binary systems, having mass in the range 0.8-8 M . Accordingly, in the single-degenerate WD scenario (Nomoto et al 2000), the rate of explosions of SN Ia can be written as…”
Section: Type Ia Supernovaementioning
confidence: 99%
“…However, the metallicity dose not seem to have the ability to interpret the whole scatter in the maximum luminosity of SNe Ia (Timmes et al 2003;Gallagher et al 2008;Howell et al 2009b). Nomoto et al (1999Nomoto et al ( , 2003 suggested that the average 1 ratio of carbon to oxygen (C/O) of a white dwarf at the moment of explosion is the dominant parameter of the Phillips relation (see also Umeda et al 1999b). The higher the C/O, the larger the amount of nickel-56, and then the higher the maximum luminosity of SNe Ia.…”
Section: Introductionmentioning
confidence: 99%